ANALISIS PERANCANGAN NOSEL SUPERSONIK DENGAN MENGGUNAKAN METODE KARAKTERISTIK - SANTOSO, ARIANTO
Supersonic nozzle designed by the method of characteristic is constructed based on the behavior of flow and shock wave , in supersonic flow with expansion wave existed by wall contour. Computation within the design process is held step by step for each process of flow crossing wave lines. Design process is taken to air flow, which is assumed as non viscous fluid and ideal gas in steady two dimensional irrotational and isentropic flow. Observation to the numerical design outcome, within the variation range of flow Mach number, giving following results. Wave strength should be taken as ?e <1Â° to have a good design contour and precision. Nozzle contour, dimension for several Mach number and the tendency of its changes due to change of Mach number are shown on figures and graphs in the report. Change of height of wave center, at a certain Mach number, to change throat contour, does not cause any change on height or cross sectional area of nozzle outlet; but, the length of nozzle is changed proportional to the height of wave center. The ratio of pressure and air density, between the outlet and throat, calculated by expansion wave equations differ unsignificantly to that taken from one dimensional flow analysis. The above results b`eingbasic characteristic of design that could be applied to construct basic pattern of supersonic nozzle design using the method of characteristic.